In Memory of Bertold Burkhardt 1941-2025 - The Executive Board of Docomomo Deutschland e.V. (Docomomo Journal)
In June, Berthold Burkhardt, one of the supporters of the first hours of Docomomo, passed away. He was involved in the organization of the International Docomomo Conference at Bauhaus Dessau (1992), and actively participating in the “restart” of Docomomo Germany in 2006. He studied architecture and civil engineering in Stuttgart (1960-1965). As an architect and engineer in Frei Otto’s office, he was involved in iconic buildings such as the German Pavilion at Expo 67 in Montreal and the roof structures for the 1972 Olympic Games in Munich. As a staff member of Institute for Lightweight Structures at the University (ILEK) in Stuttgart and in research projects, he devoted himself scientifically to the topic that occupied him throughout his entire professional life: lightweight structures. In 1984 he was appointed as professor and Head of the Institute for Structural Design at TU Braunschweig. He was able to combine his research with architectural teaching and his work as an independent architect, from 1993 together with Martin Schumacher in the Burkhardt + Schumacher office. Conservation and renovation projects became increasingly important, e.g. the employment agengy in Dessau by Walter Gropius and the Chancellor’s Bungalow in Bonn by Sep Ruf. Next to his active involvement in Docomomo, he was a member of ICOMOS, Europa Nostra, the Alvar Aalto Society, the Koldewey Society for Historical Building Research and the Society for the History of Building Technology, and served several years as head of the monitoring group for the German World Heritage Sites. As an expert and advisor, he supported the Wüstenrot Foundation and the Bauhaus Dessau Foundation, and played a key role in setting the course for the general refurbishment of the Bauhaus building from 1996 onwards. We will miss him as an architect, engineer, scientist, mentor and friend.